1983
DOI: 10.1002/jlac.198319830206
|View full text |Cite
|
Sign up to set email alerts
|

Synthese des Lycopodium‐Alkaloids rac‐α‐Obscurin durch 1,3‐Anellierung eines Enimins

Abstract: Die saurekatalysierte 1,3-Anellierung von 1,2,3,4-Teirahydro-6-methyl-2-oxopyridin (1) an das Enimin 3 liefert nach anschlieRender Methylierung regio-und stereoselektiv ruc-a-Obscurin (5).Reduktion von rac-N-Desmethyl-a-obscurin (4) rnit Lithiumaluminiumhydrid fuhrt zur Bildung von rac-Lycodin (11) und rac-Desacetylflabellidin (9). Fur das P-Amino-Imin 9 wird ein neuer Biogeneseweg vorgeschlagen. Acid catalysed 1,3-annulation of 1,2,3,4-tetrahydro-6-methyI-2-oxopyridine (1) to the enimine 3, followed by methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Enamide 8 was in turn envisioned to arise from an acid-promoted formal cycloaddition of 9 and 10 following the precedent of Schumann for the synthesis of racemic N -desmethyl-α-obscurine ( 17 , Scheme 2). 12…”
mentioning
confidence: 99%
“…Enamide 8 was in turn envisioned to arise from an acid-promoted formal cycloaddition of 9 and 10 following the precedent of Schumann for the synthesis of racemic N -desmethyl-α-obscurine ( 17 , Scheme 2). 12…”
mentioning
confidence: 99%
“…In the former study, Fischer and Sarpong started the synthesis [140] from tetracyclic compound 123 following the procedure developed by Schumann and Naumann (Scheme 20). [141] The authors converted triflated lycodine derivative 124 into boronic ester 125 under reductive detriflation conditions, followed by an Ir I -catalyzed Miyaura–Hartwig C–H borylation. [142] Pd-based cross-coupling between 125 and triflate 124 , followed by cleavage of the Boc group, produced (+)- 94 .…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%
“…Among many studies worldwide, a Japanese team isolated pelletierine from pomegranate root bark following Hess' procedure, made a comparison with data provided by Hess and Eichel and concluded that the so-called pelletierine (129) sample of pelletierine sulfate isolated by Tanret himself and showed the presence of a ketone instead of an aldehyde, confirming that the pelletierine of Tanret was 1-(2-piperidyl)-2-propanone [100]. Part of the questioning concerning the exact structure of pelletierine (129) found its roots in the epimerization that is now a well-known phenomenon with 129 and is believed to be a base-catalyzed reaction operating via retro-Michael intermediate 180. The curious history of this small molecule has been brilliantly analyzed with an historical perspective in the 1960s [101].…”
Section: Pelletierine: a Small Alkaloid With A Long Historymentioning
confidence: 99%
“…Simple biosynthetic hypotheses may be put forward to explain the formation of senepodine G, a possible direct precursor of cermizine C through iminium reduction. Despite no mention of biosynthesis, their first approach started from pelletierine (129) and is worth noting as an interesting example of the conversion of one simple natural product into another (Scheme 1.60). Despite no mention of biosynthesis, their first approach started from pelletierine (129) and is worth noting as an interesting example of the conversion of one simple natural product into another (Scheme 1.60).…”
Section: When Chemical Predisposition Does Not Follow Biosynthetic Hymentioning
confidence: 99%
See 1 more Smart Citation